Common occurrence of divergent Cryptosporidium species and Cryptosporidium parvum subtypes in farmed bamboo rats (Rhizomys sinensis) - Li, Falei; Zhang, Zhenjie; Hu, Suhui; Zhao, Wentao; Zhao, Jianguo; Kváč, Martin; Guo, Yaqiong; Li, Na; Feng, Yaoyu; Xiao, Lihua (Parasites & vectors, 2020)
BACKGROUND: Bamboo rats are widely farmed in southern China for meat, but their potential in transmitting pathogens to humans and other farm animals remains unclear. METHODS: To understand the transmission of Cryptosporidium spp. in these animals, 709 fecal samples were collected in this study from Chinese bamboo rats (Rhizomys sinensis) on nine farms in Jiangxi, Guangxi and Hainan provinces, China. They were analyzed for Cryptosporidium spp. using PCR and sequence analyses of the small subunit rRNA gene. Cryptosporidium parvum, C. parvum-like and C. ubiquitum-like genotypes identified were subtyped by sequence analysis of the 60 kDa glycoprotein (gp60) gene. RESULTS: Altogether, Cryptosporidium spp. were detected in 209 (29.5%) samples. The detection rate in samples from animals under two months of age (70.0%,105/150) was significantly higher than in samples from animals above 2 months (18.6%, 104/559; χ2 = 150.27, df = 1, P < 0.0001). Four Cryptosporidium species/genotypes were identified: C. parvum (n = 78); C. occultus (n = 1); a new genotype that is genetically related to C. ubiquitum (n = 85); and another new genotype that is genetically related to C. parvum (n = 44). Among them, C. parvum (27,610 ± 71,911 oocysts/gram of feces) and the C. parvum-like genotype (38,679 ± 82,811 oocysts/gram of feces) had higher oocyst shedding intensity than the C. ubiquitum-like genotype (2470 ± 7017 oocysts/gram of feces) and the C. occultus (1012 oocysts/gram of feces). The C. parvum identified belonged to three subtypes in two rare subtype families, including IIpA9 (n = 43), IIpA6 (n = 6) and IIoA15G1 (n = 9), while the C. parvum-like and C. ubiquitum-like genotypes generated very divergent gp60 sequences. CONCLUSIONS: Results of the present study suggest that bamboo rats on the study farms were infected with diverse Cryptosporidium species and divergent C. parvum subtypes, which probably had originated from their native habitats. As similar C. parvum subtypes have been recently detected in humans and farmed macaques, attentions should be paid to the potential role of these new farm animals in the transmission of zoonotic pathogens.
Keywords: protozoální DNA; Zoonoses; China; molekulární epidemiologie; Feces; polymerázová řetězová reakce; oocysty; Genotype; kryptosporidióza; Subtype; Cryptosporidium parvum; Cryptosporidiosis; Molecular Epidemiology; zoonózy; Zoonotic; DNA, Protozoan; Muridae; geny rRNA; Oocysts; Animals; Genes, rRNA; lidé; farmy; Humans; zvířata; Molecular epidemiology; Bamboo rat; Cryptosporidium; genotyp; Farms; Polymerase Chain Reaction; Čína; feces